Lead induced changes in biomimetic and physiological attributes of Soybean (Glycine max) - Akhtar, Nasreen; Mudassar, Muhammad Akhlaq; Hussain, Syed Saqlain; Yasin, Mubashra; Hoshide, Aaron Kinyu; Fan, Manman; Wu, Jingtao (Journal of Pure and Applied Agriculture, 2025)
Glycine max is a plant that is widely used in traditional medicine. The aim of this study was to assess the growth, physiological responses, and bioaccumulation and translocation of lead (Pb) in different tissues of soybean under different doses of Pb. In this study, plants were irrigated with Pb contaminated water, and different treatments of contaminated water were prepared by adding 20, 40, 60, 80, 100 mg Pb L-1 along with distilled water as a control. The plants were subjected to treatment in three phases (i) 65 days after sowing, (ii) 72 days after sown, and (iii) 79 days after sowing. The pots were placed in randomized complete design (CRD), and each treatment was replicated three times. Results show that biomasses of shoot, root, and pods were significantly (p < 0.05) reduced by 63.88 to 78.98% in comparison to control treatment. Likewise, 100 mg Pb L-1 treatments resulted in a decrease in the number of pods, number of seeds, and 100 seed weight by 46-67 to 66.70% in comparison to control treatment. In this study, Pb treatments significantly reduced different gaseous traits of soybean i.e., net photosynthetic rate (A), transpiration rate (E), and stomatal conductance (Gs) thereby increased CO2 concentration in the plant tissues (Ci). Higher dose of Pb (e.g. 100 mg Pb L-1) reduced the value of A by 58.55% as compared to the control treatment. Similarly, 100 mg Pb L-1 treatment decreased chlorophyll score by 65.13% over that of the control treatment. Furthermore, we observed higher bioaccumulation factors (BAF) and reduced translocation factors (TF) under higher doses of Pb. Moreover, Pb stress negatively correlated (r ranged from -0.95 to -0.99) with A, E, Gs and chlorophyll scores. It is concluded that Glycine max L. Merrill had a low tolerance against Pb toxicity. Moreover, Pb toxicity due to accumulation seeds could pose a health risk.